Educational Challenges to Human Resource Development in Islamic Education Institutions - M. Ali Haidar; Mizanul Hasanah; Muhammad Anas Ma`arif (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
One of the important resources in management is human resources (HR) or human resources. The importance of human resources needs to be realized by all levels of management, including management, the importance of human resources needs to be realized at all levels of management, including the management of Islamic education. This study uses a literature study research method. The problems outlined include (1) Human resources in educational institutions (2) Problems and challenges of Islamic education and (3) the development of human resources in Islamic educational institutions in responding to the challenges of the times. The author aims to analyze the problems and challenges of human resources in Islamic educational institutions so that they are able to respond to world challenges and continue to exist to accompany the quality of national education.